Experimental Design as Archeological Practice - Diego Gómez-Venegas (Diseña, 2018)
This article presents an approach to design which is understood as an archaeological practice; that is, an inquiry that —from the Foucauldian theories— seeks to unravel the epistemic orders embedded in the machines; to show the modes of knowing they install in culture, and in society. Thus, the archaeology of knowledge is introduced as investigative approach within the realm of human sciences and, then, as a methodology for the analysis of culture in the field of media studies, through Friedrich Kittler’s and Wolfgang Ernst’s ideas. Then, an experimental design project, a thesis of the Universidad de Chile, is commented on to exemplify the modes in which such perspective transforms the activity of design and its disciplinary categories. Finally, the text draws a methodological proposal for this design, mapping out an institutional context where this proposal can be developed in full.